Satellite remote sensing : Applications of ERS-I synthetic aperture radar for deriving coastal zone information - Seeni Mohd, Mohd. Ibrahim (1995)
The use of radar remote sensing in the microwave region of the electromagnetic spectrum has many advantages in comparison with optical remote sensing in the Visible and infrared wavelengths. By far the most important factor is the virtual insensitivity of radar to atmospheric conditions. This allows the regular collection of site observations independent of cloud coveror time ofoverpLl$S. On the other hand, the interpretation of radar imagery over land and ocean is not as straightforward as the more commonly used visible and infrared remote sensors. Usually special image processing techniques must be applied on the radar imagery to make it more readily interpretable. Furthermore, the interpretation of the backscattering process that underlies the radar image formation must be well understood with respect fa the physical characteristics of the targets under observation and the specifics of the radar instrument. This paper reports on some of the results of a study that has been carried out to derive coastal zone information from multi-Temporal synthetic aperture radar (SAR) data of the ERS-l satellite over the coastal areas of Terengganu, Malaysia. Digital image processing of the SAR data has been made that includes filtering, texture processing and Fast Fourier Transform ([1FT) for ocean wave spectra generation. Some of the features that have been identified on the processed SAR data include oil slicks, ocean waves, river outflows, breakwaters. ship and ship wakes. Some land features such as natural forest. plantations and paddy fields can also be recognised.